Answer:
x=-4,y=3
Step-by-step explanation:
[tex]\[y=-5x-17\][/tex] -------------------- (1)
[tex]\[x+y=-1\][/tex] ------------------------(2)
Substituting the value of y from (1) in (2):
[tex]\[x+(-5x-17)=-1\][/tex]
Simplifying,
[tex]\[x-5x-17=-1\][/tex]
[tex]\[=>-4x-17=-1\][/tex]
[tex]\[=>-4x=17-1\][/tex]
[tex]\[=>-4x=16\][/tex]
[tex]\[=>x=16/(-4)\][/tex]
[tex]\[=>x=-4\][/tex]
Substituting the value of x in (1):
[tex]\[y=-5*(-4)-17\][/tex]
[tex]\[=>y=20-17\][/tex]
[tex]\[=>y=3\][/tex]
The required solution is x=-4,y=3